The Effect of Beak Length and Condition on Food Intake and Feeding Behaviour of Hens - Glatz, P.C. (International Journal of Poultry Science, 2002)
Hens (70 weeks-of-age) with short (10-11 mm), long (13-15 mm) and divided           upper beaks (1-3 mm difference in beak length between the left and right           sides of the upper beak) were selected from a flock of hens beak trimmed           at hatching and re-trimmed at 14 weeks. Hens were switched from a mash           diet to various whole grain diets at weekly intervals in order to determine           the effect of beak length and condition on food intake, feeding behaviour           and particle mix consumed from diets. Birds switched from a mash diet           to a mixture of whole grain diets suffered a 22.6 g/day drop (P